The Application of the Reading Aloud Method to Improve Beginning Reading Skills in Lower Grade UPT SDN Panyirapan - Puspitasari, Widiya; Ulfiani, Eka; Ahmad Muttaqin; Lukmanul Hakim (Journal of Innovation and Research in Primary Education, 2025)
Beginning reading skills are an important foundation in the development of student literacy. However, many elementary school students in Indonesia still struggle to master reading skills at the beginning stage. These difficulties can impact students' academic achievements and interest in learning at the next level. This research aims to explore the process of implementing the loud reading method to improve the initial reading skills of second-grade students at UPT SDN Panyirapan. The focus of this research includes the experiences of students and teachers as well as the dynamics of learning in the classroom. The approach used is a qualitative approach with a case study design. The participants in this study consisted of 35 students and teachers who were purposively selected. Data collection techniques include participatory observation, in-depth interviews, and documentation. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The research results show that the application of the read-aloud method has a positive impact on improving students' technical reading skills, such as reading fluency, pronunciation, and intonation. In addition, this method also increases students' active participation in reading activities, fosters learning motivation, and strengthens comprehension of the reading material. Thus, the read-aloud method can serve as an effective alternative learning strategy to address beginning reading issues in elementary schools. These findings are expected to serve as a reference for teachers and education policymakers in designing more engaging and meaningful reading instruction for students.